2018
DOI: 10.23937/2469-5823/1510090
|View full text |Cite
|
Sign up to set email alerts
|

Social Correlates of Nurses' Preparedness towards Retirement in Zaria, Northwest Nigeria

Abstract: Pension decree 102 of 1979 age constitution of the Federal Republic of Nigeria Section 3 (1) and (2) Stipulates the various types of retirement: Voluntary retirement or withdrawal after qualifying services, retirement after attaining the maximum statutory age of 60 years or length of service of 35 years. There are also retirements for the purpose of facilitating improved efficiency or economy or for public interest and retirement due to total or permanent disablement.Retirement planning is an exercise in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Two quantitative studies have explored workplace stress among health workers in Nigeria, including doctors, nurses and midwives. They provide an insight into the levels of adversity experienced by health workers (Anyebe et al, 2014;Ladan et al, 2014). Findings from these studies concluded that a high incidence of occupational stress-related burnout among nurses and midwives existed.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Two quantitative studies have explored workplace stress among health workers in Nigeria, including doctors, nurses and midwives. They provide an insight into the levels of adversity experienced by health workers (Anyebe et al, 2014;Ladan et al, 2014). Findings from these studies concluded that a high incidence of occupational stress-related burnout among nurses and midwives existed.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…A shortage of staff with many patients to care for, a lack of adequate equipment, long working hours and poor communication with colleagues were identified as some of the major causes of workplace stress. (Anyebe et al, 2014;Ladan et al, 2014). However, there is a lack of qualitative studies into all health care worker's experiences and also a lack of midwifery specific studies to enhance the understanding of the findings.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…For nurses, a departure from work to retirement transition could present a significant nerve-racking experience of adjustment, professional role-identity detachment, and adaptation challenges ( Uthaman et al, 2016 ). Thus, retirement transition among nurses might raise depression and preretirement anxiety ( Anyebe et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Nigerian nursing profession and its work environment face many preretirement emotions ( Nnadozie et al, 2022 ). For instance, working as a Nigerian nurse is one of the most demanding professions as a result of a lack of retirement preparedness due to their empathetic nature toward lifesaving ( Anyebe et al, 2018 ), increased workload with fewer incentives, and increased fatigue severity ( Nnadozie et al, 2022 ) and decreased financial self-efficacy ( Arogundade, 2016 ). These experiences may also be aggravated by the issues of Nigerian nurses comparing themselves with their contemporaries working in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation